Rancang Alat Pembelah Rotan Sebagai Material Alternatif Yang Ramah Lingkungan - Abd Kadir; Prinob Aksar; Bahdin Ahad Badia; Salimin Salimin; Citra Yurnidar Syah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Rattan is an environmentally friendly alternative material with significant potential for the handicraft industry, particularly in Southeast Sulawesi. However, the rattan splitting process is still predominantly performed manually, resulting in low efficiency, long processing time, and increased occupational safety risks. Therefore, this study aims to design and evaluate the performance of a semi-automatic rattan splitting machine that is efficient, ergonomic, and environmentally sustainable. The research methodology includes the stages of design, manufacturing, assembly, and performance testing . Performance tests were carried out by comparing the splitting time between manual methods and the proposed machine, using rattan diameters ranging from 10 mm to 20 mm. The results indicate that the designed rattan splitting machine significantly improves processing efficiency and production capacity, produces more uniform split results, and reduces material waste. In addition, the machine demonstrates efficient fuel consumption, making it suitable for small- to medium-scale handicraft industries, the proposed machine provides a practical solution to enhance productivity, economic efficiency & environmental sustainability in rattan processing industries